Anatomic variability of the intercostal neurovascular bundle in human fetuses. - Okrim, I. I. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Studying the features of fetal topography of the intercostal neurovascular bundle in fetuses of different ages allows establishing general biological patterns of morphogenesis, typical structure and topography of structures of intercostal spaces, age and individual anatomical variability of intercostals nerves and posterior intercostals vessels. Objective – to clarify the peculiarities of the topography of the intercostals neurovascular bundle components in human fetuses aged 4-10 months. Methods. The study involved 70 specimens of human fetuses with 81.0-375.0 mm of crown-rump length by macro-microscopic dissection, injection of blood vessels, superficial staining of the dissected vessels and nerves as well as morphometry. Results. During the fetal period of ontogeny, there is an age and individual anatomical variability of intercostals neurovascular bundles, which is manifested by variability of structure, topography and number of their constituents, asymmetry of topography of right and left posterior intercostals vessels and nerves, different branching of the posterior intercostals arteries and nerves, by a variety of the development of the system of the azygos vein and its tributaries, both in fetuses of different and of the same age group or even in the same fetus. Conclusions. The trunks of adjacent intercostals nerves and posterior intercostals vessels are connected by means of connecting branches. Therefore, during operations on the lateral chest wall, one should be mindful of anastomoses between the vessels and nerves of adjacent intercostals spaces that realize the effect of cross-vascularization and innervations of the structures of the chest wall. Besides, connecting branches go from the nodes of the thoracic section of the sympathetic trunk to the intercostals nerves. The variants of the topography and branching of the intercostals nerves and posterior intercostals arteries in the intercostals spaces and the peculiarities of out flow of venous blood from their posterior areas should be taken into account by fetal and neonatal surgeons during surgery.